Satisfacción percibida del usuario externo de la atención de enfermería en las estrategias sanitarias, Hospital Distrital De Laredo, 2015 - Ruiz Charcape, Sandra Nelcy (2015)
This research descriptive cross-sectional; it was realized at the Laredo District Hospital, in order to determine the level of satisfaction perceived by the external user on nursing care health strategies performed in outpatient clinic. The sample consisted of 235 users who were treated by nurses in health strategies. The modified SERVQUAL survey by the authors was used to collect data. The information obtained was processed and analyzed in SPSS version 19 and Microsoft Excel version 2010 and presented in tables. The results indicate that 73.6% of external users are satisfied with nursing care, 23% are unsatisfied and 3.4% are indifferent. Conclusions: More than a half of external users who were attended by the Health Strategies are satisfied. The dimension with the highest percentage of satisfaction is the capacity of answering and the less satisfaction is empathy.